2002
DOI: 10.1200/jco.2002.20.6.1506
|View full text |Cite
|
Sign up to set email alerts
|

Volume of Lymphatic Metastases Does Not Independently Influence Prognosis in Colorectal Cancer

Abstract: The number of nodes involved with metastatic tumor, rather the volume of metastatic involvement of the regional lymph nodes, predicts outcome. These results suggest that micrometastatic disease may have a similar prognosis as macrometastatic disease when the same number of lymph nodes are involved with metastatic tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 24 publications
0
5
0
2
Order By: Relevance
“…In addition, the VCP level proved to be a prognosticator for recurrence of the disease in lymph node-positive patients (stage III) as well as node-negative patients (stage II): 5-year disease-free survival rate in patients with low and high VCP expression was 100 and 72.8% at stage II and 100 and 48.4% at stage III, respectively. Although lymph node metastasis is an indicator of poor prognosis of patients with colorectal carcinomas, heterogeneity of the prognosis among patients with positive lymph nodes has been a problem (20). The present study has clearly demonstrated the usefulness of VCP expression in predicting distant metastasis in node-positive patients.…”
Section: Discussionmentioning
confidence: 56%
“…In addition, the VCP level proved to be a prognosticator for recurrence of the disease in lymph node-positive patients (stage III) as well as node-negative patients (stage II): 5-year disease-free survival rate in patients with low and high VCP expression was 100 and 72.8% at stage II and 100 and 48.4% at stage III, respectively. Although lymph node metastasis is an indicator of poor prognosis of patients with colorectal carcinomas, heterogeneity of the prognosis among patients with positive lymph nodes has been a problem (20). The present study has clearly demonstrated the usefulness of VCP expression in predicting distant metastasis in node-positive patients.…”
Section: Discussionmentioning
confidence: 56%
“…Survival rates have been shown to decrease with increasing numbers of positive lymph nodes. Nodal metastasis is commonly small, and evidence suggests that patients with micrometastasis in multiple nodes by H&E examination may have an outcome similar to patients with multiple macrometastasis (22). Conversely, high numbers of negative lymph nodes have been correlated with better survival.…”
Section: Lymph Node Special Techniquesmentioning
confidence: 99%
“…We are aware of only one previous study assessing metastasis volume in CRCs [35]. In that study, total nodal volume was estimated on the basis of two-dimensional histological slides, and was found to be in weak correlation (correlation coefficient: r ¼ 0.45, P-value not reported) with the number of LNs involved.…”
Section: Discussionmentioning
confidence: 94%